Implementation of Aqidah Akhlak Learning: An Observational Study of the Role of Teachers in Managing Teaching and Learning Activities in Madrasah Ibtidaiyah - Sofiana, Ira Agus; Ogy Yan Hesta; Rofik Andi Hidayah; M.A Dhalu; Sri Rahmawati (IAIN KENDARI, 2026)
This study aims to describe the implementation of Aqidah Akhlak learning and the role of teachers in managing teaching and learning activities in Madrasah Ibtidaiyah. The research was conducted in three Madrasah Ibtidaiyah located in the Pondok Aren area, South Tangerang City. The research method used was a qualitative approach with data collection techniques through direct observation of the learning process in the classroom. The observation focused on lesson planning, lesson implementation, the role of teachers as role models of morals, classroom management, learning evaluation, as well as obstacles and efforts of teachers in implementing learning. The results showed that the planning of Aqidah Akhlak learning had been well prepared in terms of objectives, materials, and methods, although the use of learning media still needed to be developed. The implementation of learning was structured and conducive, with teachers able to create an active, enjoyable, and meaningful learning atmosphere by relating the material to the students' daily lives. Teachers also played an effective role as role models of good character, were able to manage the classroom in an educational manner, and carried out comprehensive learning evaluations that covered cognitive aspects and changes in student behavior. However, this study found challenges in the form of limited learning media and variations in methods, so that more interactive learning development is needed so that the implementation of Aqidah Akhlak learning can run more optimally and have a sustainable impact on the character building of students.